HSBP1 Is a Novel Interactor of FIP200 and ATG13 That Promotes Autophagy Initiation and Picornavirus Replication - Mario Mauthe (Frontiers Media S.A., 2021)
ATG13 and FIP200 are two subunits of the ULK kinase complex, a key regulatory component of the autophagy machinery. We have previously found that the FIP200-ATG13 subcomplex controls picornavirus replication outside its role in the ULK kinase complex and autophagy. Here, we characterized HSBP1, a very small cytoplasmic coiled-coil protein, as a novel interactor of FIP200 and ATG13 that binds these two proteins via FIP200. HSBP1 is a novel pro-picornaviral host factor since its knockdown or knockout, inhibits the replication of various picornaviruses. The anti-picornaviral function of the FIP200-ATG13 subcomplex was abolished when HSBP1 was depleted, inferring that this subcomplex negatively regulates HSBP1’s pro-picornaviral function during infections. HSBP1depletion also reduces the stability of ULK kinase complex subunits, resulting in an impairment in autophagy induction. Altogether, our data show that HSBP1 interaction with FIP200-ATG13-containing complexes is involved in the regulation of different cellular pathways.